EXPERIENCE OF THE HOLY, IN THE TECHNOLOGICAL AGE: (AN INTERVIEW) - Ott, Heinric (Journal of Dharma, 1993)
Heinrich Ott rose to prominence in the late nineteen-fifties primarily on the basis of his strikingly original alignment of Karl Barth and Martin Heidegger. Influenced by both, but a significant theologian in his own right, Ott has inaugurated a remarkable programme in hermeneutics and ontology. In executing his programme, or as Ott might prefer, in undertaking his theological journey, his path has crossed, or at times run parallel, to Heidegger’s path of thinking. Consequently, it’s not that surprising when the Journal of Dharma met with Ott in Basel early last year, much of our dialogue focused on Heidegger’s analysis of technology and Ott’s account of what this means for the doing of contemporary theology.